Pantograph Lifting Collision Characteristics under Complex Working Conditions - WEI Haifei; ZHOU Ning; LI Mudi; ZHANG Weihua; ZHANG Min; SHI Changyou; WU Kaiyang (Chengshi guidao jiaotong yanjiu)
［Objective］To investigate the dynamics issues arising from the frequent lifting and lowering of pantographs in multi-mode hybrid traction trains, the pantograph collision characteristics are analyzed. ［Method］Taking the PC (pantograph-catenary) system as research object, a PC collision test bench is built to study the dynamics characteristics of pantograph collisions during the lifting process. A corresponding dynamics model is established and validated using experimental data. The variation patterns of vertical collision contact forces are also analyzed. ［Result & Conclusion］During PC collisions, collision speed and contact wire stagger value both significantly affect the maximum value, standard deviation, and dynamic coefficient of PC vertical contact force. As the collision speed increases, both the standard deviation and the maximum value of the vertical contact force increase accordingly, while the dynamic coefficient initially decreases and then increases, reaching its minimum when the collision speed is 0.5 m/s. As the stagger value increases, the standard deviation of the vertical collision contact force decreases. At a lower collision speed, the maximum value of the vertical contact force decreases with the increasing collision speed. Conversely, at a higher speed, the minimum vertical contact force initially decreases and then increases, reaching a minimum around a stagger value of 200 mm. Across all speed conditions, the dynamic coefficient is highest when there is no stagger and reaches its lowest point around a stagger value of 400 mm.